Improvement of Human Thinking Factors In Machine Using Artificial Intelligence (International Journal of Engineering and Computer Science, 2016)
Now a day the machine became as much as intelligent like human. The machine don’t have their own intelligence logic so in the modern science we need to have a human thinking logic which can be made incorporate in the machine to improve their intelligence factor. Increasing machine intelligence leads to a shift from a mere interactive to a much more complex cooperative human-machine relation requiring a multidisciplinary development approach. This paper presents a generic multidisciplinary cognitive engineering method (CE+) for the integration of human factors and artificial intelligence in the development of human machine cooperation. For each system design the method supports research and development activities in such a way that sound knowledge bases, methodologies, and user interfaces for human-machine cooperation could be established. However, the method always needs to be tailored to the specific goals and circumstances, such as the available time, novelty, and required integration.